2017
DOI: 10.1177/1756827717711016
|View full text |Cite
|
Sign up to set email alerts
|

Two-step approach for pressure oscillations prediction in gas turbine combustion chambers

Abstract: Currently, gas turbine manufacturers frequently face the problem of strong acoustic combustion-driven oscillations inside combustion chambers. These combustion instabilities can cause extensive wear and sometimes even catastrophic damage of combustion hardware. This requires prevention of combustion instabilities, which, in turn, requires reliable and fast predictive tools. We have developed a two-step method to find a set of operating parameters under which gas turbines can be operated without going into self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Iurashev et al. 50 studied the BRS burner shown in Figure 13 with a hybrid approach: first, the FTF of the flame was calculated with CFD, giving data points in the frequency range [0,…500 Hz]. This FTF data was approximated by an analytical expression representing a low-pass filter with damping and a time-lag τ.…”
Section: Intrinsic Thermoacoustic Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Iurashev et al. 50 studied the BRS burner shown in Figure 13 with a hybrid approach: first, the FTF of the flame was calculated with CFD, giving data points in the frequency range [0,…500 Hz]. This FTF data was approximated by an analytical expression representing a low-pass filter with damping and a time-lag τ.…”
Section: Intrinsic Thermoacoustic Modesmentioning
confidence: 99%
“…Flame modelled by FTF from CFD simulations Iurashev et al 50 studied the BRS burner shown in Figure 13 with a hybrid approach: first, the FTF of the flame was calculated with CFD, giving data points in the frequency range [0,. . .500 Hz].…”
Section: Intrinsic Modes In a Laboratory Swirl Burner -mentioning
confidence: 99%
“…When the length of the setup under consideration is much larger than its dimensions in the other directions, it is possible to perform a one-dimensional low-order acoustic analysis (Bellucci et al, 2005;Schuermans et al, 2010;Bothien et al, 2015;Iurashev et al, 2016b).…”
Section: Wave-based Approach For Thermoacoustic Simulationsmentioning
confidence: 99%
“…In order to connect oscillating variables in different sections (see Figure 2), we need to know the jump conditions. To compute the jump conditions between sections separated by a compact acoustic element, such as sharp cross-sectional area change and a compact swirler, the system of linearised equations of conservation of mass and Bernoulli (Dowling and Stow, 2005;Iurashev et al, 2016b) written in terms of f and g is solved.…”
Section: Wave-based Approach For Thermoacoustic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation